2014
DOI: 10.15835/nbha.42.2.9447
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salicylic Acid on the Growth, Photosynthetic Efficiency and Enzyme Activities of Leguminous Plant under Cadmium Stress

Abstract: The present study was designed with an objective to elucidate the effect of the exogenous application of 10 -5 M of salicylic acid (SA) to the foliage of the chickpea plants exposed to 0, 25, 50 or 100 mg cadmium (Cd) per kg of soil. The foliage of the plants grown in soil amended with varying doses of Cd was sprayed with 10 -5 M of SA at 30 days after sowing (DAS). The plant samples were collected at 60 and 90 DAS to assess various parameters. The damage caused due to the Cd exposure was partially overcome by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…In fact, decreased Rubisco activity by Cd stress has been attributed due to the low activity of CA or Cd-Mg replacement in active centers in Cd-stressed plants (Siedlecka et al 1998). Similar SA mediated increase in CA activity under Cd stress was reported by Alyemini et al (2014) and Ahmad et al (2018).…”
Section: Discussionsupporting
confidence: 62%
“…In fact, decreased Rubisco activity by Cd stress has been attributed due to the low activity of CA or Cd-Mg replacement in active centers in Cd-stressed plants (Siedlecka et al 1998). Similar SA mediated increase in CA activity under Cd stress was reported by Alyemini et al (2014) and Ahmad et al (2018).…”
Section: Discussionsupporting
confidence: 62%
“…Ecologically, rice can survive under water for a short period due to adaptive physiological mechanisms including enzymatic and non-enzymatic factors [ 10 , 11 ]. Regarding the former factor, an antioxidant enzyme system has been discovered in plants subjected to biotic and abiotic stresses producing numerous varieties of activated oxygen species consisting of superoxide, singlet oxygen, hydroxyl radicals, and hydrogen peroxide [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dry weight was higher in SA treated plants as compared to Pb + Ni treatment (T3). Alyemeni et al (2014) also found a significant increase of dry mass of Cicer arietinum plants with the application of 10 -5 M salicylic acid.…”
Section: Plant Growthmentioning
confidence: 71%